Imbrication: Reading a South African life - Burns, Catherine (PINS-Psychology in Society, 2024)
The temporal context opens in the early years of World War II, in a small village in the then Union of South Africa, and tracks a seven-decade search for meaning and truth by the author. Manganyi is a pre-eminent reader of the world and its texts – embodied, scripted, literary, critical and performed. The method of life, exemplified in this memoir, is of the reader, in Alberto Manguel’s explication of the term, with reading as an active, archaeological, erudite, committed, passionate and dialogical skill.